SMART SHOPPING TROLLEY IN SHOPPING MALLS USING IOT (International Journal of Food and Nutritional Sciences, 2022)
Nowadays, buying and searching for products at shopping malls are turning into a daily activityin cities. We can see many number of people shopping at malls on holidays and weekends. The rushhappens when there are special offers and discounts. People purchase completely various things and placethem in trolley.